Pengaruh Live Streaming dan Online Customer Review Terhadap Keputusan Pembelian Pada Produk Vaseline di Shopee - Ambiya, Khoerul; Fauji, Robby (Peneliti.net, 2024)
The rapid progress of technology in the last decade has meant that several aspects of life have changed significantly. This progress is felt globally, especially in Information Technology. Characterized by activities that are transformed from the traditional to the digital era. The marketplace platform that is often used to process online transactions in Indonesia is Shopee. Indonesian people often access this marketplace platform during the first to third quarter of 2023. This study examines how live broadcasting and online customer reviews affect Shopee Vaselie purchases. According to positivism, a quantitative research method with a verification and descriptive approach is an objective, tangible, methodical, and logically measurable scientific procedure used to evaluate theories with hypotheses. Research data collection uses questionnaires. The research was conducted on Buana Perjuangan University Karawang students who used Vaseline Body Lotion on Shopee, both men and women. Research findings show that live streaming has a big impact on purchasing decisions for Vaseline products. In addition, online customer evaluations have limited influence on Vaseline product purchasing decisions. The convergence of live streaming and online customer reviews has significantly influenced the choice of purchasing Vaseline products on the Shopee platform. It is hoped that this research can contribute to products being marketed online through marketplaces or other e-commerce